Low doses of recombinant human erythropoietin does not affect C‐terminal FGF23 in healthy men. Issue 7 (6th April 2020) - Bejder, Jacob; Robach, Paul; Lundby, Anne‐Kristine; Cornu, Catherine; Sallet, Pierre; Cairo, Gaetano; Lundby, Carsten
Abstract: Recombinant human erythropoietin (rhEpo) can improve human performance, but misuse remains difficult to detect. C‐terminal fibroblast growth factor 23 (cFGF23) was recently demonstrated to increase following injection of a single high dose rhEpo, but the effect of more frequent low doses is unknown. Using a randomized double‐blind placebo‐controlled design, we investigated whether 2 weeks of subcutaneous injections three times a week of 50 IU/kg Eprex (low‐dose) or 20 IU/kg Eprex (micro‐dose) increase cFGF23 levels compared with saline (placebo) injections in 24 healthy males. Venous blood was sampled at day −3, 0, 1, 3, 11, 14, 18, and 25 of the treatment and analyzed for cFGF23 and erythropoietin concentration ([EPO]). The level of cFGF23 was similar at days −3, 0, 1, 3, 11, 14, 18, and 25 with the low‐dose (23 ± 4, 26 ± 5, 23 ± 7, 27 ± 6, 25 ± 8, 24 ± 10, 22 ± 5, and 24 ± 7 RU/mL, respectively), micro‐dose (23 ± 6, 25 ± 5, 23 ± 8, 28 ± 9, 27 ± 7, 25 ± 9, 25 ± 5, and 23 ± 6 RU/mL, respectively) and placebo (23 ± 6, 24 ± 6, 26 ± 7, 26 ± 6, 31 ± 6, 31 ± 7, 24 ± 4, and 27 ± 8 RU/mL, respectively) treatment. The correlation coefficient between plasma [EPO] and plasma cFGF23 levels was R 2 = 0.01 and insignificant. The results demonstrate that cFGF23 is not sensitive to low doses of subcutaneous rhEpo injections in healthy males. Abstract :